Produção de ésteres biolubrificantes de alto valor agregado utilizando catalisadores heterogêneos sulfônicos - Marques, João Paulo Cordeiro (2021)
In this work, synthesis and characterization of biolubricant esters, the production and characterization of biolubricant blends and the catalytic study of polystyrene sulfonated (PSSA) and polystyrene sulfonated supported on silica matrix (SiO2-PSSA) were performed. In the first part of the work, it was evaluated the influence of linear and branched side chains on the biolubricants physicochemical properties. Four biolubricants (ISO 32) were synthesized from oleic acid. These syntheses occur from the route of esterification, with 1-octanol and 2-ethylhexanol, epoxidation and oxirane rings opening, with 1-octanol and 2-ethylhexanol, using Amberlyst 15 as catalyst. The physicochemical properties were measured and the reactions were monitored by 1H NMR. The biolubricant with branched side chains showed best cold property (PP = -6 °C) and the one with linear side chains showed better oxidative stability (EO = 3.19 h). In the second part of the work, it was evaluated the influence of the unsaturated fatty acids concentration of the raw material on the biolubricants physicochemical properties. Three biolubricants (ISO 32) were synthesized from soybean oil derivatives. These syntheses occur from the route of esterification/transesterification with 2-ethylhexanol, epoxidation and oxirane rings opening with 2-ethylhexanol, using Amberlyst 15 as catalyst. The physicochemical properties were measured and the reactions were monitored by 1H NMR. The biolubricant synthesized from the raw material with the highest concentration of unsaturated fatty acids showed best cold behavior (PP = -12 °C) and the one synthesized from soybean biodiesel showed the best application properties (PP = -6 °C, EO = 2.33 h and IA = 0.19 mg KOH/g). The thermogravimetric analysis of the samples showed that the concentration of unsaturated does not influence the thermal behavior and that the evaluated products suffer two thermal events: volatilization and combustion. In the third part of the work, it was evaluated the use of di-2-ethylhexyl sebacate as a bioadditive. The bioproduct was synthesized from the esterification reaction of sebacic acid with 2-ethylhexanol, using Amberlyst 15 as catalyst. The physicochemical properties of the blends were measured and the reaction was monitored by 1H NMR. The bioproduct was able to produce biolubricant blends with three viscosity degrees (ISO 15, ISO 22 and ISO 32) and improve the physicochemical properties of a synthesized biolubricant, mainly the pour point, which reached -24 °C in an isovolumetric blend. In the fourth part of the work, two catalysts in the study of the oxirane rings opening reaction, PSSA and SiO2-PSSA were tested. The reactions were monitored by 1H NMR. A first test showed that PSSA had better catalytic properties (100% conversion) than SiO2-PSSA (9% conversion). Subsequently, it was performed a more robust catalytic study with the PSSA, where it was possible to evaluate that: the higher the catalyst percentage, the higher the conversion (10% catalyst; 100% conversion); the ideal reaction temperature is 50 °C (lowest temperature; 100% conversion); after 1 h, the conversion stabilizes; and until the third reaction cycle, with the catalyst recovered, there was not reduction in catalytic efficiency.